Otrokova čustvena doživljanja materine bolezni rak dojke - Šmit, Majda (Obzornik zdravstvene nege, 2005)
The present article describes children's experiencing of their mother's breastcancer. The aim of the research was to ascertain how discussing the disease among mother and her children affects their emotional experiencing. The author analyzed case studies of five mothers with breast cancer and their eight children. Data were gathered by interviews, carried out in March 2002. The answers were processed by means of qualitative text analysis. The results revealed prevalent negative emotional experiencing during the periods of diagnostic and treatment process which reveals distress in children when they were told that their mother has fallen ill with breast cancer and about the treatment process. Positive emotional experiencing showed up after the mothersdiscussed the situation with their children and explained it according to their ability of understanding. In conclusion, the importance of nonverbal communication and candid talking in the family are stressed, as well as their impact upon the quality of life of both, mothers who have fallen ill and theirchildren.
Keywords: ankete; breast; Breast Neoplasms; Child; čustva; Dojka, novotvorbe; dojke; matere; Mati-otrok, odnosi; Mother-Child Relations; otroci; Otrok; psihologija; psychology; Questionnaires; rak (medicina)